Deflation and economic growth in long-term perspective - Pavel Ryska (Charles University in Prague, Institute of Economic Studies (IES), 2014)
This paper deals with the relationship between deflation and economic growth. Although there are numerous theories on the potential effects of deflation on real output, empirical evidence in this field is still scarce and partial. In order to explore the relationship between prices and output in a more comprehensive way, I use a large panel data set of 19 countries over roughly 150 years, which contains frequent deflationary episodes. I employ the fixed effects model to look at both contemporaneous and lagged correlation between prices and output, and I include control variables to remove potential bias. There are several important results. First, there is no general relationship between prices and output. The lagged negative effect of deflation on output growth, alleged by some authors, disappears after adding a control variable. Second, monetary regimes seem to affect the relationship. Deflation appears to become associated with output slightly negatively with the advent of the fiat money system, while it was benign under the classical gold standard. Third, well-known episodes of deflation differ a lot. The Great Depression is the only period where deflation seems to be strongly associated with recession. By contrast, Japan in the 1990s and 2000s bears no resemblence to it. Here, both empirically and theoretically, deflation is highly unlikely to have caused economic stagnation.
Keywords: E31; E42; C33; N10; 330; deflation; price level; economic growth; monetary systems; panel data; economic history